Inhibition of Hepatitis C Replication by Targeting the Molecular Chaperone Hsp90: Synthesis and Biological Evaluation of 4, 5, 6, 7‐Tetrahydrobenzo[1, 2‐d]thiazole Derivatives. (22nd January 2019) - Lillsunde, Katja‐Emilia; Tomašič, Tihomir; Schult, Philipp; Lohmann, Volker; Kikelj, Danijel; Tammela, Päivi
Abstract: Cellular chaperones that belong to the heat‐shock protein 90 (Hsp90) family are a prerequisite for successful viral propagation for most viruses. The hepatitis C virus (HCV) uses Hsp90 for maturation, folding, and modification of viral proteins. Based on our previous discovery that marine alkaloid analogues with a 4, 5, 6, 7‐tetrahydrobenzo[1, 2‐ d ]thiazole‐2‐amine structure show inhibition of HCV replication and binding to Hsp90, a series of twelve novel compounds based on this scaffold was designed and synthesized. The aim was improved Hsp90 affinity and anti‐HCV activity. Through structural optimization, improved binding to Hsp90 and specific HCV inhibition in genotype 1b and 2a replicon models was achieved for three compounds belonging to the newly synthesized series. Furthermore, these compounds efficiently inhibited replication of full‐length HCV genotype 2a in a reporter virus RNA assay with IC50 values ranging from 0.03 to 0.6 μm . Abstract : New compounds going viral : Twelve compounds were designed and synthesized based on the 4, 5, 6, 7‐tetrahydrobenzo[1, 2‐ d ]thiazole‐2‐amine scaffold. The aim was to achieve antiviral activity against hepatitis C virus (HCV) by targeting Hsp90, a cellular protein essential for HCV propagation. Improved binding to Hsp90β was accomplished and compounds2, 5, and8 were found to inhibit replication of full‐length HCV genotype 2a with IC50 values of 0.03 μm (5 ), 0.1 μm (8 ), and 0.6 μm (2 ).